Pemberian Penyuluhan Bencana Banjir terhadap Kesiapsiagaan Siswa Kelas VI Menghadapi Bencana Banjir - Ni Luh Kompyang Sulisnadewi; I Ketut Labir (Jurnal Gema Keperawatan, 2017)
The purpose of this research was to know the influence of providing flood disaster counseling toward 6th grade students’ preparedness facing flood disaster. This reasearch used Pre-Experimental Design which plans One Group Pretest-Posttest using simple random sampling. The sample was 80 students from 100 population. The result of the research shows that students preparedness before conducting counseling most of the students who are ready is only 32 students (40%) and after counseling students’ preparedness is increased to 38 students (47,5%). The research was measured by using Wilcoxon statistic test, ρ-value = 0,000 alpha (0,05), can be concluded there is influence of flood counseling toward 6th students preparedness to face flood disaster at SDN 11 Padangsambian.